Метод получения начальных размещений в задаче моделирования структуры систем плотноупакованных объектов - Чугай, А.М. (Проблемы машиностроения, 2014)
На основе квази Ф-функций построена математическая модель задачи плотной упаковки неориентированных выпуклых многогранников в параллелепипеде минимальной высоты. На основе особенностей построенной модели предложен метод получения различных начальных размещений многогранников. Метод состоит из трех основных этапов. На первых двух решаются вспомогательные задачи нелинейного программирования, которые позволяют получить начальное размещение многогранников. На последнем этапе определяются параметры разделяющих плоскостей для квази Ф-функций. На основі квазі Ф-функцій побудовано математичну модель задачі щільного пакування неорієнтованих опуклих багатогранників у паралелепіпеді мінімальної висоти. На основі властивостей побудованої моделі запропоновано метод отримання різноманітних початкових розміщень багатогранників. Метод складається з трьох основних етапів. На перших двох вирішуються допоміжні задачі нелінійного програмування, які дозволяють отримати початкове розміщення багатогранників. На останньому етапі визначаються параметри відокремлюваних площин для квазі Ф-функцій. In this paper a mathematical model of a dense packing problem of non-oriented convex polytopes into a cuboid of minimum height is constructed by using the quasi Ф-function. An application of quasi Ф-functions allows to formulate mutual non-intersections conditions for a pair of objects as a set of inequalities systems left sides of which are infinitely differentiable functions. Owing to this fact a mathematical model of the problem is presented as a classical non-linear programming problem. For construction of different starting points a special method is proposed. The method includes three stages. On the first and second stages helper problems are solved. The first helper problem allows us to find a covering of polytopes by spheres of minimal radius. The second one allows us to find a dense packing of spheres in an arrangement region. At the third stage parameters of separating planes between the dense packing spheres are calculated.